"Making up" workers in an inclusive organisation: Inclusion and diversity in Danish parking patrol. Issue 3 (2014) - ,
Abstract : Purpose – The purpose of this paper is to investigate the unintended consequences of managing inclusion and diversity and how these unintended consequences relate to organisation members' mediation between work tasks and practices of inclusion and diversity.Design/methodology/approach – The study uses critical diversity and inclusion studies as the theoretical context and a Danish municipal centre responsible for parking patrol as the empirical context. The researcher has conducted interviews and participant observation in this organisation and particularly analyses the "making up" of abstract categories of employees and the mundane "making of" employees in the light of diversity and inclusion practices.Findings – The analysis shows that parking attendants are "made up" as an increasingly professionalised brand and that the inclusive policy of diversity becomes part of this brand. However, the study also shows that in spite of this external brand, local and internal practices of inclusion and diversity create categories of people that employees may avoid or resist and some that carry unfulfilled promises of inclusion. Moreover, an internal image of the parking attendant as a person on the edge of the labour market persists internally in spite of the effort to brand this person otherwise externally.Originality/value – The paper applies the notion of "making up" people, to accommodate critique of the social constructionist approach, that is common to much critical research on diversity and inclusion. Furthermore, the paper agitates for "bringing work back in" to the study of diversity and inclusion and does this by focusing on the work of parking attendants. Given that this work is formally unskilled, the organisation represents an example of a workplace that represents a gateway to the Danish labour market, which makes the management and organisation of inclusion very pertinent. The paper provides new perspectives, particularly in terms of the unintended consequences of inclusion in organisations.